Digital Innovation and Effective Management to Expand the Market for Taro Chips with Zero Waste Concept in Wanagiri Village, Buleleng, Indonesia - Suriati, Luh; Datrini, Luh Kade; Prayoga, I Kadek Mahabojana Dwi; Mardewi, Ni Ketut; Chindrawati, Anak Agung Sagung Manik; Damayanti, Ni Luh Putu Sulis Dewi; Putra, I Putu Ajus Raditya; Putri , Ni Kadek Sintya Pradnyani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community engagement project aimed to empower local microenterprises in Wanagiri Village, Buleleng, by introducing digital innovation and effective business management to enhance the production and market expansion of taro chips. Two main community partners, the PKK women's group and the Wanagiri Youth Taro Processing Group (KPT), previously relied on conventional methods with limited market reach and minimal waste utilisation. The intervention implemented a five-phase strategy: (1) socialisation and stakeholder mapping, (2) training and technology introduction, (3) hands-on practice, (4) mentoring, and (5) evaluation and sustainability planning. Key outputs included standardised hygienic production processes (GMP/SSOP), financial bookkeeping systems, digital marketing capability through social media and marketplaces, new branding and packaging, and a prototype for processing taro waste into animal feed. The program significantly improved partners' production volume, quality, digital literacy, and business sustainability. This initiative demonstrates how community-based digital innovation and management capacity building can transform local agribusinesses, increase household income, and contribute to sustainable rural development. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 9: Industry, Innovation, and Infrastructure